2020
DOI: 10.1007/s12015-020-10017-6
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells Therapy as a Possible Therapeutic Option in Treating COVID-19 Patients

Abstract: An unfortunate emergence of a new virus SARS-CoV-2, causing a disease known as COVID-19, has spread all around the globe and has caused a pandemic. It primarily affects the respiratory tract and lungs in some cases causing severe organ damage and pneumonia due to overwhelming immune responses. Clinical reports show that the most commons symptoms are fever, dry cough, and shortness of breath, along with several other symptoms. It is thought that an immense cytokine dysregulation in COVID-19 patients is caused f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…Because COVID-19 was first officially reported in China, it is unsurprising that 34% of these trials were registered in China. In China, a total of 30…”
Section: Country and Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Because COVID-19 was first officially reported in China, it is unsurprising that 34% of these trials were registered in China. In China, a total of 30…”
Section: Country and Statusmentioning
confidence: 99%
“…However, due to many ethical and legal restrictions, clinical development and progression of stem cell therapies have been relatively slow 29 . Because adult stem cells are exempt from the aforementioned ethical and legal restrictions, while possessing excellent tissue repair capabilities, usage of adult stem cells has been more popular than embryonic or pluripotent stem cells in the clinic 30 . Accumulating studies have shown that stem cell therapy is becoming one of the emerging treatment strategies for several refractory diseases with no known treatments, including viral infections 31 .…”
Section: Potential Mechanisms Of Stem Cell Therapy In Covid‐19mentioning
confidence: 99%
“…The virus is enveloped in a spherical nucleocapsid. The genomic pool of SARS-CoV-2 consists of + ssRNA in association with nucleoprotein inside a capsid shell [ 9 ]. At the external surface of the envelope, numerous projections (Spike proteins) and glycoproteins (hemagglutinin) are seen.…”
Section: Covid-19 Pathophysiology and Mechanism Of Actionmentioning
confidence: 99%
“…Given the severe onset of COVID-19 related tissue damage at a systemic level in extreme cases, the application of stem cell engineering to repair and regain organ functionality has been explored and adapted from other applications to quickly answer the need for potential therapeutic solutions (Ji et al, 2020). The usage of nano scaffolds based on biocompatible polymers for tissue engineering using mesenchymal stem cells (MSCs) has thus emerged in articles as a promising experimental therapeutic option for patients at a critical stage to reduce inflammation, enhance immunomodulation and promote tissue repair back to a functional level (Esquivel et al, 2020). A summary of the potential uses of this technology is briefly discussed.…”
Section: Tissue Engineering For Immunomodulation and Replacement Of Tissues Damaged By Covid-19mentioning
confidence: 99%